2021
DOI: 10.53088/jmdb.v1i2.49
|View full text |Cite
|
Sign up to set email alerts
|

Mengukur minat berwirausaha dengan menggunakan pendekatan theory of planned behavior dan religiusitas

Abstract: The purpose of this study was to examine the effect of behavioral attitudes, subjective norms, perceived behavioral control, and religiosity on interest in entrepreneurship. This type of research is quantitative research. The population used is students of the Faculty of Economics and Islamic Business, Salatiga State Institute of Islamic Religion, with the criteria for students who have taken entrepreneurship courses. The number of samples taken was 271 students with a proportional stratified random sampling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
3
0
4
Order By: Relevance
“…Furthermore, Fikrianoor et al (2021) argued that religiosity significantly positively affects the entrepreneurial intention of students in Indonesia. Other empirical studies suggested the effect of religiosity on the entrepreneurial intention of students in Indonesia (Maullah and Rofiuddin, 2021). Hence, the research hypothesis is: H1.…”
Section: Religiosity and Entrepreneurial Intentionmentioning
confidence: 93%
“…Furthermore, Fikrianoor et al (2021) argued that religiosity significantly positively affects the entrepreneurial intention of students in Indonesia. Other empirical studies suggested the effect of religiosity on the entrepreneurial intention of students in Indonesia (Maullah and Rofiuddin, 2021). Hence, the research hypothesis is: H1.…”
Section: Religiosity and Entrepreneurial Intentionmentioning
confidence: 93%
“…Pengetahuan kewirausahaan merupakan ilmu tentang tanggapan peluang usaha yang terungkap dalam seperangkat tindakan yang membuahkan hasil berupa organisasi usaha yang melembaga produktif dan inovatif (Mardiyatmo, 2005:2). Berdasarkan teori TPB, kerangka berpikir konseptual yang memiliki tujuan untuk memengaruhi sikap seseorang saat melakukan sesuatu adalah sikap berperilaku, norma subjektif, dan persepsi control perilaku (Maullah & Rofiuddin, 2021).…”
Section: Pendahuluanunclassified
“…Literasi keuangan adalah suatu pengetahuan dan pemahaman mengenai konsep keuangan dan kecakapan dalam pengelolaan keuangan dalam hal pengambilan keputusan pada situasi tertentu. Berdasarkan teori TPB, kerangka berpikir secara konseptual menjelaskan bahwa literasi keuangan memengaruhi sikap seseorang saat melakukan sesuatu adalah sikap berperilaku, norma subjektif, dan persepsi control perilaku (Maullah & Rofiuddin, 2021).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Hal ini sesuai pada indikator mengambil resiko usaha, menganalisis peluang usaha, merumuskan solusi masalah, dimana mahasiswa mempunyai pengetahuan kewirausahaan yang baik yaitu mampu menganalisis peluang usaha serta mampu merumuskan solusi-solusi permasalahan yang ada sehingga nantinya dapat menimbulkan keyakinan berupa kendali dalam berani mengambil resiko usaha dan akan menumbuhkan minat mahasiswa untuk berwirausaha. Dengan adanya presepsi kontrol perilaku yang kuat dan tidak memiliki keraguan pada tantangan serta segala resiko yang mungkin akan dihadapi, maka seseorang akan semakin mantap untuk berwirausaha (Maullah & Rofiuddin, 2021).…”
Section: Pembahasanunclassified